2019
DOI: 10.1038/s41598-018-37532-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of position one variants within the lantibiotic nisin

Abstract: Lantibiotics are a growing class of natural compounds, which possess antimicrobial activity against a broad range of Gram-positive bacteria. Their high potency against human pathogenic strains such as MRSA and VRE makes them excellent candidates as substitutes for classic antibiotics in times of increasing multidrug resistance of bacterial strains. New lantibiotics are detected in genomes and can be heterologously expressed. The functionality of these novel lantibiotics requires a systematic purification and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 71 publications
6
37
0
Order By: Relevance
“…This variant served as a negative control in all our experiments. The lack of NTP hydrolysis for Sa NsrF H202A is in line with in vivo studies that show that this variant abolishes the activity of Sa NsrFP 8 , 40 .…”
Section: Resultssupporting
confidence: 80%
“…This variant served as a negative control in all our experiments. The lack of NTP hydrolysis for Sa NsrF H202A is in line with in vivo studies that show that this variant abolishes the activity of Sa NsrFP 8 , 40 .…”
Section: Resultssupporting
confidence: 80%
“…According to these studies the observed high secretion efficiency of NisA by NisBTC was explained by a ‘channeling mechanism’ 19 , 35 . Other studies focused on the application of the nisin modification machinery to produce nisin variants or lantibiotics and secrete them by NisT 36 39 . Despite the in vivo analysis of NisA secretion, a first analysis with labeled precursor peptides was performed and gave first insights into the kinetics of secretion 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and quantification of the active lantibiotic by integrating the leader peptide peaks in RP-HPLC might be complicated due to alteration of running properties of the pre-lantibiotics and activated forms during the experiment and make it difficult to distinguish between similar peaks. This strategy has been used to determine the concentration of the activated lantibiotic during the production of genome-mining new lantibiotics as a hybrid containing the leader peptide of nisin (Lagedroste et al, 2019).…”
Section: Practical Expression Purification Monitoring Strategies Amentioning
confidence: 99%
“…Later, the lipid-II binding activity of some lantibiotics was also demonstrated ( Wiedemann et al, 2001 ; Breukink and de Kruijff, 2006 ), although in some of them the mechanisms of action have yet to be clarified. Nonetheless, low cytotoxicity of lantibiotics to human cells due to the absence of their main target lipid II or negative net charge in eukaryotic membranes ( Lagedroste et al, 2019 ) along with a few examples of naturally occurring resistance ( Draper et al, 2015 ; Khosa et al, 2016a,b ; Clemens et al, 2018 ) make lantibiotics excellent lead compounds for development of new therapeutic options.…”
Section: Lanthipeptides Are Ribosomally Produced and Post-translationmentioning
confidence: 99%